Impact of potentially inappropriate medication and continuity of care in a sample of Taiwan elderly patients with diabetes mellitus who have also experienced heart failure. Issue 10 (23rd October 2015) - Lai, Yung‐Rung; Yang, Yi‐Sun; Tsai, Min‐Ling; Lu, Ying‐Li; Kornelius, Edy; Huang, Chien‐Ning; Chiou, Jeng‐Yuan
Abstract : Aims: Continuity of care (COC) and potentially inappropriate medication (PIM) can affect the elderly healthcare outcome. We evaluated the COC and PIM effects in older diabetes mellitus (DM) patients with heart failure (HF). Methods: The Longitudinal Health Insurance Database of 2005 was multiple‐year claim data collected from 2005 to 2010 in Taiwan. There were both 823 DM and non‐DM subjects aged 65 years and older in this observational study. The COC index and 2012 Beers criteria were applied to evaluate the COC and HF‐PIM in older DM patients with heart failure. The dependent variables were either hospital admissions or emergency department visits. Generalized estimating equation was used to adjust all covariates. Results: During 2005–2010, the rate of HF‐PIM in the elderly DM group was 86.1%, the mean COC index was 0.28 ± 0.19, the admission rate was 31.9% and the emergency department rate was 38.8 %. Lower COC index was associated with HF‐PIM and HF‐PIM duration in older DM patients with HF. Lower COC index was associated with hospitalizations (OR 0.07, 95% CI 0.05–0.11) and ED visits (OR 0.10, 95% CI 0.07–0.13), but HF‐PIM was not significant. The duration of HF‐PIM was related with poor health outcomes over 90 and 180 days for hospitalization and emergency department visit, respectively. Conclusion: Among elderly DM patients with HF, COC had positive effects on healthcare outcomes. Improving COC and reducing PIM duration for elderly DM patients with HF seems warranted.Geriatr Gerontol Int 2016; 16: 1117–1126.